Optimization of device control for the flicker perimeter. - Wu, Jie. (University of Ottawa (Canada), 2002)
To optimize the function of a prototype flicker perimeter, it is important to reduce the amount of time required to change test target location in the visual field while maintaining the random presentation order necessary to ensure accurate results. The purpose of this project is to develop and test a software algorithm that achieves these two goals simultaneously. I have developed an algorithm for the Flicker perimeter that maximizes the efficiency of travel in the motors governing test target projection. This will reduce the time between test trials as well as the entire sequence, thus limiting the fatigue factor in testing. The algorithm incorporates a component that maintains a pseudo-random order of presentation. I have developed and constructed a simulation of the functioning perimeter by designing and reengineering the system program and incorporating both the original presentation algorithm (Random) and the optimizing algorithm (Optimized). (Abstract shortened by UMI.)
Keywords: Engineering, System Science.